PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN PENGUNGKAPAN CSR TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2019) - Fardelia Safira, Della; Tituk Diah Widajantie (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The Company has short-term and long-term. In the short term the company aims to maximize current profits, while in the long term it aims to increase the value of the company itself. This research aimed to examine and analyze the effect of profitability, company size, leverage, and CSR disclosure to the value of manufacturing companies listed on the IDX in 2015-2019. While, the sampling collection technique used purposive sampling with 10 samples which fulfilled the criteria. The data analysis technique used multiple regression linear with SPSS (Statistical Product and Service Solutions). In this research, the testing variable of profitability used Return On Asset (ROA), company size used total assets, leverage used Debt to Equity Ratio (DER), CSR used Corporate Social Disclousure Index (CSDI), and the value of the company used Tobins’Q. The research result concluded that: (1) profitability effect the value of the company, (2) company size did not effect the value of the company, (3) leverage did not effect the value of the company, (4) CSR disclosure effect the value of the company. Keywords: Profitability, Company Size, Leverage, CSR Disclosure, and the value of the company.